Avatar : the last airbender. The promise. Part three - Yang, Gene Luen; Konietzko, Bryan; DiMartino, Michael Dante (Avatar . Last Airbender., 2012)
The Harmony Restoration Movement has failed, and the four nations are plunged back into war! In the midst of the battle, can Aang and Fire Lord Zuko mend the rift between them, or will Aang be forced to take actions that can't be undone?